Effect of evening postexercise cold water immersion on subsequent sleep - Robey, E.; Dawson, B.; Halson, S.; Gregson, W.; King, S.; Goodman, C.; Eastwood, Peter (2013)
PURPOSE: This study investigated the effect of cold water immersion after evening exercise on subsequent sleep quality and quantity in trained cyclists. METHODS: In the evenings (~1900 h) on three separate occasions, male cyclists (n = 11) underwent either no exercise (control, CON), exercise only (EX), or exercise followed by cold water immersion (CWI). EX comprised cycling for 15 min at 75% peak power, then a 15-min maximal time trial. After each condition, a full laboratory-based sleep study (polysomnography) was performed. Core and skin temperature, heart rate, salivary melatonin, ratings of perceived fatigue, and recovery were measured in each trial. RESULTS: No differences were observed between conditions for any whole night sleep measures, including total sleep time, sleep efficiency, sleep onset latency, rapid eye movement onset latency, wake after sleep onset, or proportion of the night spent in different sleep stages. Core temperature in EX and CWI trials was higher than CON, until it decreased below that of EX and CON until bedtime in CWI. After bedtime, core temperature was similar for all conditions throughout the night, except for a 90-min period where it was lower for CWI than EX and CON (3.5-4.5 h postexercise). Heart rates for EX and CWI were both significantly higher than CON postexercise until bedtime, whereas skin temperature after CWI was significantly lower than EX and CON, remaining lower than EX until 3 h postexercise. Melatonin levels and recovery ratings were similar between conditions. Fatigue ratings were significantly elevated after exercise in both CWI and EX conditions, with EX still being elevated compared with CON at bedtime. CONCLUSION: Whole night sleep architecture is not affected by evening exercise alone or when followed by CWI. Copyright © 2013 by the American College of Sports Medicine.